To what extent can flipped learning strategies enhance the success of SRL in A Level Economics - Larner, C (2020)
This research looks to support the deeper learning of A-level economists through assessing the merits of flipped learning to improve the use, and success, of self-regulated learning (SRL). With a focus on autonomy, self-efficacy and self-assessment cycles, successes were expected not only through improved academic results but also by enhancing students’ wider transferable skills for use beyond 6th form education.